A Data Mining Method for Refining Groups in Data Using Dynamic Model Based Clustering - Servi, Tayfun; Erol, H. (IEEE, 2013)
A new data mining method is proposed for determining the number and structure of clusters, and refining groups in multivariate heterogeneous data set including groups, partly and completely overlapped group structures by using dynamic model based clustering. It is called dynamic model based clustering since the structure of model changes at each stage of refinement process dynamically. The proposed data mining method works without data reduction for high dimensional data in which some of variables including completely overlapped situations. © 2013 IEEE. © 2013 Elsevier B.V., All rights reserved.
Servi, Tayfun/0000-0002-3173-327X; Erol, Hamza/0000-0001-8983-4797
Keywords: Data Mining; Dynamic Model Based Clustering; Refining Groups In Data; Data Mining Methods; Group Structure; Heterogeneous Data; High Dimensional Data; Model Change; Model-Based Clustering; Refinement Process; Dynamic Models; Intelligent Systems; Refining; Data Mining